THE DEVELOPMENT OF MEDIA SCRAPBOOK ON ANY MATERIAL A VIRUS TO BASICALLY INCREASED THE MOTIVATION TO STUDY A STUDENT OF SENIOR HIGH SCHOOL CLASS X - Syafiatul khusna; eva nurul malahayati; dwi kameluh agustina (JOSAR (Journal of Students Academic Research), 2018)
This research aim to know the properness of scrapbook media on virus material and to increase student learning motivation after using scrapbook media for the tenth grade of senior high school. This research is Research and Development (RnD) by applying the Borg and Gall development model which is limited to the seventh stage. Data were analyzed by qualitative descriptive analysis. The average rating by experts is 80.06% with eligible criteria. The increasing student learning motivation was 19.21%. Based on the results of the study it can be concluded that scrapbook media on virus material for the tenth grade of senior high school is proper to be used in learning process and increase student learning motivation.